Multilayers fast mode decision algorithm for scalable video coding: design, implementation, and streaming evaluation on IEEE 802.11g wireless LAN - Maarif, Haris Al Qodri; Gunawan, Teddy Surya (Lambert Academic Publishing, 2011)
Nowadays the advancement of technologies has reached the massive growth and commercial success in multimedia and mobile communication. The advancement and development in video coding technology, together with the increase of storage capacity network infrastructures and computing power are enabling an increasing number of video applications.